Penerapan Casework Pada Klien Dengan Gangguan Bicara Di Taman Penitipan Anak Permata Kisaran - Fathiyyah Nurul Izzah; Agus Suriadi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Delay or speech disorders in children is one of the problems of child development. Children who experience speech delays, namely when children are 2 years old, but tend to experience errors in pronouncing words, then when they are 3 years old children have poor vocabulary or lack of vocabulary understanding. According to IDEA (Individuals with Disabilities Education Act) 1997, speech disorders refer to communication disorders such as stuttering, articulation disorders, language disorders and voice disorders. Cases of children with speech delays were also found at the Permata Kisaran Child Care Park. This case was discovered when the practitioner was doing the Field Work Practice I at the place. Children who experience speech delays will be at risk of hampering the socialization process. When carrying out the socialization process, verbal communication is one way that is always practiced. If the child's words cannot be understood, then the communication process does not run effectively. Furthermore, it will affect self-confidence, feel inferior because others do not understand what is conveyed. To overcome client problems, the practitioner uses the casework intervention method which has previously been assessed using SWOT analysis techniques, interviews and observations.